2010
DOI: 10.1007/s10439-010-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in the Molecular Stability of Collagen from the Pulmonary and Aortic Valves During the Fetal-to-Neonatal Transition

Abstract: During the fetal-to-neonatal transition, transvalvular pressures (TVPs) on the aortic and pulmonary valves change dramatically-but differently for each valve. We have examined changes in the molecular stability and crosslinking of collagen during this transition. Aortic and pulmonary valves were harvested from fetal and neonatal cattle. Using differential scanning calorimetry (DSC), denaturation of valvular collagen was examined and, using HPLC, the types and quantities of enzymatic crosslinks were examined. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Thus, a higher proportion of immature cross-links indicates a more rapid turnover rate of collagen (1,4). Treatment of our tissues with NaBH 4 significantly increased HIT t 1/2 for tissues from all pregnancy groups, indicating the presence of thermally labile, immature crosslinks.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, a higher proportion of immature cross-links indicates a more rapid turnover rate of collagen (1,4). Treatment of our tissues with NaBH 4 significantly increased HIT t 1/2 for tissues from all pregnancy groups, indicating the presence of thermally labile, immature crosslinks.…”
Section: Discussionmentioning
confidence: 83%
“…Further, in a recent study that examined collagen hydrothermal stability of heart valve tissues, it was found that collagen in heart valves subjected to higher TVP had lower molecular stability and cross-linking (3). The molecular stability of the collagen in the AV also decreased compared to that of the PV from transition from fetal to neonatal when the TVP in the AV increases due to closure of the foramen ovale and ductus arteriosus (2). Aldous et al speculated from these findings that a relationship exists between the turnover rate of collagen and mechanical loading whereby there is a faster rate of damage accumulation and collagen turnover in the valves under higher TVP as a mechanism of resistance to biomechanical fatigue loading.…”
Section: Discussionmentioning
confidence: 99%
“…Further, at 90 mmHg the PV VIC undergoes a much larger deformation than the AV VIC, which can be reached in pulmonary hypertension or the Ross procedure. Hence, different levels of VIC deformation may lead to modification of ECM gene expression and architecture, as seen with age, disease, or repair (1, 2, 7, 19, 27). This information sets the foundation for a more detailed study on VIC tissue formation and remodeling as a function of hemodynamic loading and VIC-collagen micromechanical coupling.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen fibers are one of the key players in the remodeling process, since these proteins are the main load-bearing component of many soft tissues. In particular, collagen fiber orientation and bundle formation through cross-linking [8,9] play a significant role in valvular tissue mechanics. As a consequence, the architecture of the collagen network has a major influence on the mechanical functionality of soft tissues, as well as on mechanically induced growth and remodeling processes.…”
Section: Introductionmentioning
confidence: 99%